Humoral and Mucosal-Humoral Immune Response to a Salmonella vaccination Program in Broiler Breeders - Bailey, J.S.; RolÃ³n, A.; Holt, P.S.; Hofacre, C.L.; Wilson, J.L.; Cosby, D.E.; Richardson, L.J.; Cox, N.A. (International Journal of Poultry Science, 2007)
Although vaccination against Salmonella has been used more frequently in broiler breeders in recent years, there is limited information in the literature demonstrating the immunological response of combinations of live and killed whole cell vaccines. The present research assesses the immunological response generated by three different vaccination protocols. Treatment vaccines consisted of a live Aro-A mutant commercial Salmonella Typhimurium (ST) vaccine (Fort Dodge Animal Health) and a commercially prepared killed vaccine consisting of a pool of Salmonella serovars Berta (D1), Heidelberg (B) and Kentucky (C2). Three vaccination treatments using live, killed or a live-killed combination plus a non-vaccinated control were evaluated. Serum (SER), Crop Lavage (CL), Gut Lavage (GL), hatchling serum and egg yolk were tested for specific IgA and IgG anti-Salmonella Enteritidis (SE) or Salmonella Typhimurium lipopolysaccharide (SELPS or STLPS, respectively) antigen by indirect ELISA. Immunological response was stronger on STLPS than SELPS. IgA of SER and CL were short-lived peaks after the first killed vaccine, with Optical Densities (OD) greater than 1.000. A short-lived peak of IgG of CL on STLPS (OD>1.500) was also observed. Strong GL IgG after first live and both killed vaccine events were observed (OD>1.000), with the response to the killed preparation enduring longer. SER IgG responses observed after killed vaccination lasted throughout 40 wks of age with no demonstrable differences between treatments. Hatchling serum and egg yolk IgA were negligible and IgG was comparable among all treatments throughout time. Results confirm that killed antigen is vital in eliciting adequate IgG in serum and gut. Live vaccination with Aro-A mutant ST vaccine enhances gut IgG and possibly aids in conferring adequate immunity during the breeder’s first wks of life